Impacts of Border in Borderland Conflict along the Ethio-Sudan Border: Evidence from Metema Woreda, North-Western Ethiopia - Temesgen Eyilet Kebede (Humaniora, 2020)
The aim of the study is to understand the dynamics of borderland conflicts in one location –Gonder, north-west Ethiopia, specifically, Metema Woreda – which lies along the Ethiopia-Sudan border. The study employed qualitative research methods such as semi-structured interviews, focus group discussions, case studies, and non-participant observation. The colonial origin of the Ethio-Sudan border is the overall background to the confrontation between farmers and investors over the contested lands in the region. The continued uncertainty over the precise location of the border has aggravated conflict that has yet to be resolved.